Petrology of the neoproterozoic Cape Granite Suite hosted W-Mo-REE Riviera endoskarn deposit with special reference to allanite characteristics - Santana, Monica Manuela (Stellenbosch : Stellenbosch University, 2015)
Thesis (MSc)--Stellenbosch University, 2015.